Implementation of Work Environment Hygiene and Sanitation Standard in Public Health Facilities Sumbawa - Iga Maliga; Rafi'ah Rafi'ah; Herni Hasifah; Abdul Hamid (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: The implementation of sanitation standards and cleanliness of the work environment in health care facilities is an absolute must. Hospital Sanitation is an effort by the health care system in hospitals to create clean, comfortable, healthy hospital conditions, prevent cross-infection, and not discuss the environment. Objectives: This study aimed to determine the application of hygiene and sanitation standards to the work environment in health care facilities. Research Metodes: This study uses quantitative methods using a descriptive design. This research was conducted at the Sumbawa Hospital, and the data collection technique used an observation system and a checklist sheet whose results were calculated using a scoring system. The time of study was carried out in November 2021. Results: The results/findings of the study showed that the achievement of implementing environmental sanitation was 90.4%, the achievement of environmental health was 91.6%, and the achievement of environmental sanitation was 92.3%. Conclusion: In conclusion, the study results indicate that the implementation of sanitation and hygiene in the work environment at the Sumbawa Hospital has met the requirements. It's just that there is still a need for improvement in aspects of environmental health implementation, especially in parts of air sanitation and waste management..